Evaluation of the Effectiveness of Using Yokke EDC in Supporting Payment Transactions at Alfamart in the Banda Aceh Region - Kiki Putri Amelia; Melvi Havizatun; Nabil Aufar (International Journal of Management Science and Information Technology, 2026)
The development of digital payment technology is driving retail merchants like the development of digital payment technology encourages retail merchants like Alfamart to provide fast and efficient transaction services. Electronic Data Capture (EDC) has become a key tool in supporting cashless payments, including Yokke EDC, which has been widely implemented at various Alfamart outlets in Banda Aceh. This study aims to evaluate the effectiveness of using the Yokke EDC based on four indicators: transaction speed, device reliability, ease of use, and customer satisfaction. This research method uses a quantitative approach with a questionnaire distributed to 35 employes. The research results indicate that Yokke EDC is considered effective in supporting payment transactions, although there are limitations such as unstable network connectivity at certain times. Overall, the Yokke EDC plays an important role in improving the quality of payment services at Alfamart Banda Aceh.